Psychology and the Education of Persons in British Columbia: A Critical Interpretive Investigation - McLellan, Ann-Marie; Martin, Jack (Canadian Journal of Education/Revue canadienne de l'éducation, 2005)
Psychological theory and research assume conceptions of the self that are highly individualistic and instrumental. When incorporated into educational theory and practice, such conceptions serve to elevate goals and strategies of self-fulfilment and individual freedom over goals and practices that emphasize citizenship and civic virtue. We present a brief, critical history of self studies in psychology as applied to education, as well as an example of the influence of psychological conceptions of the self on elementary school curricula in British Columbia. We conclude that the autonomous, self-governing individual is celebrated at the expense of the socially dependent, committed citizen. Keywords: self conceptions, psychological theory, school curricula Certaines théories et des courants de recherche en psychologie postulent lexistence dimages de soi très individualistes et instrumentales. Intégrées dans la théorie et la pratique en éducation, de telles images ont pour effet de placer les buts et les stratégies de lactualisation de soi et la liberté personnelle au-dessus des buts et des pratiques qui mettent laccent sur la citoyenneté et le civisme. Les auteurs présentent une courte histoire critique des auto-observations en psychologie dans leur application à léducation. En étudiant linfluence des conceptions de soi sur les programmes du primaire en Colombie-Britannique, ils ont trouvé que les programmes privilégiaient le sujet autonome aux dépens du citoyen engagé et socialement engagé. Mots clés: images de soi, théorie psychologique, curriculums scolaires